Digitalization: realities and simularies of parallel reality - Kutsepal Світлана (Actual Problems of Mind, 2023)
The article defines the essential features of the concept of "digitalization", which is ambiguously evaluated by researchers. It also focuses attention on the positive and negative consequences of digitalization, and defines the development trends of the digital society.Among the indisputable advantages of digitalization, the following stand out: the expansion of opportunities to meet needs of both a spiritual and material nature, a significant improvement in the quality of life, an increase in the opportunities for intellectual and creative development, an increase in the ability to career growth and opportunities for self-realization and self-development. Emphasis is made on the opportunities, open to people with disabilities, limited opportunities for employment, inclusion in the social life of those persons, who under normal conditions due to various reasons could not take an active social position is ensured.The danger of digitalization is the blurring of the boundaries between public and private life, which was especially evident during the pandemic, when a large part of the population was forced to switch to work and study online; interference in private life; the polarization of society as a result of digital inequality, which tends to deepen.It has been proved that the result of digitization is the creation of a new image of society - a digital society, where the boundary between reality and virtuality is leveled, its own system of signs reigns, and a new system of values ​​and norms is formed.Considerable attention is paid to the phenomenon of the "digital man", who exists in virtual space, creates and transforms information relationships, perceives the world as a simulation game model, is convinced of his ability to control the digital world, but at the same time is a hostage of an alternative reality generated by the digitalization process.